Organización forestal comunal y sustentabilidad en San Juan Nuevo (Michoacán): poder y conflicto en torno a los usos locales, nacionales e internacionales de la reciprocidad - Bofill Poch, Sílvia (ENDOXA, 2002)
National and regional peasant movements during the 1970s and the 1980s struggling to créate a legal and productive space for peasant carved out by State intervention did provide a space within which communities as San Juan Nuevo could organize and regain same control over their forest resources. State policies and dramatic forestry subsequent reforms during the 90s were deadened by implementing forest supporting programs, such as the National Reforestation Program within the National Solidarity Program, which presumed to reshape both productive and political relations in Mexico’s forest dependent communities. Ultimately however, state institutions as well as International supporting agencies as the World Bank, despite the rhetorical commitment to peasant production and environmental issues, largely articúlate with private industrial interests and act as mechanisms that secured control over forest resources by external interests. San Juan forestry model, preferentially supported, provides a window for understanding how industrial interests, state practices and community strategies intersect. In fact it illuminates new clientelistic strategies embedded in forest policy and neo-liberal discourse more generally, ones in direct contradiction to the solidarity’s democratic, neutral international agencies and state rhetoric.